1990
DOI: 10.2527/1990.68124334x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary level of barley-based supplements and ruminal buffer on digestion and growth by beef cattle1

Abstract: Six ruminally cannulated beef steers were used in a 6 x 6 Latin square experiment with a 3 x 2 factorial arrangement of treatments to evaluate the effects of barley supplementation (BS; 10, 30 or 50% of diet DM) and ruminal buffer (RB; Na sesquicarbonate at 0 or 4% of BS DM) addition to bromegrass hay-based diets on digestion. When early- (boot) and late- (full maturity) havested bromegrass and wheat straw substrates were incubated in situ, no interactions (P greater than .10) involving substrate with dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 0 publications
1
14
1
4
Order By: Relevance
“…The increases observed were approximately 10, 11, 13 and 30% superior to those found before feeding, respectively, for the levels 13, 15, 19 and 22 g CP/100 g DM of the diet. The ammonia non-assimilated by the microorganisms is usually absorbed by the rumen wall, removed from the portal circulation by the liver, entering the urea cycle (Lobley et al, 1995). When the rate of ammonia synthesis is higher than its utilization by the microorganisms, there is elevation in the concentration in the rumen, with consequent increase in the excretion and in the energy cost of production of urea, resulting in loss of protein (Russell et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increases observed were approximately 10, 11, 13 and 30% superior to those found before feeding, respectively, for the levels 13, 15, 19 and 22 g CP/100 g DM of the diet. The ammonia non-assimilated by the microorganisms is usually absorbed by the rumen wall, removed from the portal circulation by the liver, entering the urea cycle (Lobley et al, 1995). When the rate of ammonia synthesis is higher than its utilization by the microorganisms, there is elevation in the concentration in the rumen, with consequent increase in the excretion and in the energy cost of production of urea, resulting in loss of protein (Russell et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Analyzes of the SCFA were conducted according to method recommended by Leventini et al (1990), by means of gas chromatography (7890-A, Agilent Technologies, Palo Alto, CA, USA), equipped with flame ionization detector (7683B, Agilent Technologies, Palo Alto, CA, USA) and fused silica capillary column DB-WAX (30 m; 0.25 mm; 0.25 µm propylene glycol, Agilent Technologies, Palo Alto, CA, USA). The data acquisition was done by means of software ChemStation (Agilent Technologies, Palo Alto, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…However, Jackson et al (1992) observed a quadratic trend with the highest intake when 1.88% of BICARB was added to calves' starter diet. Leventini et al (1990) hypothesized that increases in liquid passage rate caused by BICARB addition lead to an increase in ruminal wash-out of particles with the corresponding increase in feed intake. The reduction in DMI observed at the highest level of BICARB is in agreement Effect of sodium bicarbonate level was significant at **P < 0.01, or at *P < 0.05: L 5 linear, Q 5 quadratic and C 5 cubic.…”
Section: Discussionmentioning
confidence: 99%
“…Ruminal pH has also been ameliorated in some studies (Nicholson et al, 1963;Okeke et al, 1983;Zinn, 1991), but no effects have been reported in many others (e.g. Thomas and Hall, 1984;Leventini et al, 1990). This fact could be the result of the different variables affected by buffer addition and interactions between them, such as intake level, ruminal -Present address: Animal Nutrition, Management, and Welfare Research Group, Universitat Autò noma de Barcelona, 08193-Bellaterra, Spain.…”
Section: Introductionmentioning
confidence: 99%
“…Using Whatman 64 filter paper, filtered silagc liquids and silage fluid were stored in deep freezer until they werc analyzed. Organic acid analyses were made according to method of Leventini et al (1990) using gas chromatography.…”
Section: Methodsmentioning
confidence: 99%